Treatment of Sweating, Hot Flushing and Sleep ‎Disturbance in Peri and Post Menopausal ‎Women with Oral Pometone (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Vasomotor symptoms, such as hot flushes and night sweats, are very common during the menopausal transition. One of the important alternative treatments is foods or supplements enriched with phytoestrogens.Aim of the studyTo assess the efficacy, safety and acceptability of pometone supplements for reducing sweating, hot flushes and sleep disturbance in peri and postmenopausal women.Methods This cross sectional randomized clinical therapeutic trail involved 44 peri and postmenopausal women. All patients took oral pometone capsule 500mg twice daily for one month period.Result The mean of hot flush, sweating score before treatment was 8.11±1.72. After four weeks of treatment, it became 1.36 ±2.10; P value was < 0.0001. The mean of sleep disturbance score before treatment was 4.40±3.03. After four weeks of treatment, it become 1.22 ±1.80 ; P value was  < 0.0001 . No side effect was reported during the course of this study.ConclusionPometone is effective, safe and cheep treatment to reduce hot flushes , night sweat and sleep disturbance in peri and postmenopausal women